Aprendizagem social para sustentabilidade no ensino superior: um estudo em cursos de administração de empresas - Mello, Andreza Sampaio de (2014)
Some business schools have lived the insertion of the theme sustainability in their curricula, worrying about promoting, in future administrators‟ education, the discussion about sustainability issues in this level of teaching. The objective of this research is to understand how the social learning process works for sustainability concerning two business administration courses. It adopts a theoretical reference that articulates the notion of social learning from authors who study the sustainability thematic, with the ones who investigate learning in organizations. In order to approach this thematic empirically, two case studies that made use of qualitative methodologies in their data collecting and analysis process were developed. Data collecting was performed in two private higher education institutions in the city of São Paulo, specifically in business administration courses. It evolved the exam of the institutions official documents as well as two kinds of interviews: (a) individual, with courses teacher and coordinators, (b) in groups: with students. After the interviews were performed and transcribed, data were analyzed by means of interpretative textual analysis process as well as templates. In a first moment, the analysis of the cases was made separately, but, a comparison item is presented as follows. The main results reveal that worrying about sustainability questions is highlighted in the objective and the focus of the business administration courses from both institutions researched, highlighting entrepreneurship. From the courses coordinators as well as professors testimonies it is possible to identify two great challenges that are present in the effort of integrating this theme in the process of futures business administrators education. The first one is about the adoption of an interdisciplinary approach in the proposal development and effectiveness process established in the pedagogical projects. The second one is associated with the formative process itself that, eventhough examines and discusses the sustainability theme, it reveals an individualized and fragmented treatment of the curricular actions for the theme development. Even though data show the use by the professors of diversified classroom strategies, what may give an idea of a less mechanic teaching, it is possible to infer, from the results found that professors seem to use those strategies worrying about instrumental issues in the sense of adapting the traditional management model to the perspective from the sustainability paradigm. In both institutions, it is possible to perceive that there is receptivity to the theme and that they offer resources as well as support for their strengthening in the studied courses. However, it is possible to understand that both institutions worry about marketing and search a differential in their courses concerning sustainability. The most frequent learning social processes used for sustainability approach among coordinators and professors in both institutions were: learning from sharing ideas and experiences inside the institution and learning from sharing ideas and experiences with other institutions. The content about sustainability most evidenced in the students testimonies from both institutions is that sustainability encompasses other aspects than the environmental ones. The reference used to analyze and interpret the results found showed that it is possible to understand both theoretical perspectives proposed with complementary and useful approaches for reflecting about questions evolved in the insertion of the sustainability thematic in the business administration courses.